Blended Educational Technologies in Higher Education: Systematic Review of Domestic Publications - N. V. Bordovskaya; E. A. Koshkina; M. A. Tikhomirova; L. A. Melkaya (Высшее образование в России)
The article presents the results of generalization and systematization of scientific and practical information on the variety of types of blended educational technologies used in Russian higher education institutions. This specific product of digitalization causes the greatest interest of researchers and practitioners in the field of education. This systematic review is based on national scientific publications related to the development and practical implementation of educational technologies in higher education. The authors have analyzed 180 papers published between 2016 and 2021 in peer-reviewed scientific journals approved by the Higher Attestation Commission. Methods of qualitative and quantitative content analysis, systems analysis and contextological analysis, as well as analytical grouping, have been used.Content analysis of publications showed that the main property of blended educational technologies is their variability, which manifests itself through the described system of indicators. However, the structural organization of blended educational technologies models remains the most debatable issue among researches.The authors have identified and described the main directions in the development of the theory and practical application of blended educational technologies, namely: the formation of the structure and boundaries of the conceptual and terminological field; elaboration of the methodological basis of blended education development and definition of theoretical basis for changing traditional learning systems by designing a learning process based on the mechanisms of pedagogical and digital technologies integration.It has been established that the empirical studies with the elements of experimental work focused on defining the most effective combinations of traditional and digital educational technologies dominate in the national scientific community. The most popular methods of such integration include rotation of forms and types of learning activity in traditional and digital learning environments, integration of digital and traditional educational technologies based on the Moodle learning management system, as well as inclusion of separate forms and means of e-learning in the educational process.